Pengaruh Key Performance Indicator dan Quality Control Terhadap Kinerja Karyawan Sales Marketing di PT.Indo Mai Goo (AICE) - Nugraha, M Tri Rangga; Khalikussabir, Khalikussabir; Hardaningtyas, Ratna Tri (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine and analyze the influence Key Performance Indicator and Quality Control on the Performance of Sales Marketing Employees at PT. Indo Mai Goo (AICE). The population in this research is Marketing Employees who have high integrity at PT. Indo Mai Goo (AICE). The data collection method in this research used a questionnaire with a sample size determined using the Slovin formula and the results obtained were 83 respondents. Data testing techniques used in this research include validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, f test, t test, and coefficient of determination test (Adjusted R2). The results of this research simultaneously show that the influence Key Performance Indicator (KPI) and Quality Control influence employee performance. Partially, Key Performance Indicator (KPI) and Quality Control influence employee performance. Keywords: Key Performance Indicator, Quality Control, and Sales Marketing Employee Performance.